2019
DOI: 10.1042/bcj20190242
|View full text |Cite
|
Sign up to set email alerts
|

The β-hairpin region of the cyanobacterial F1-ATPase γ-subunit plays a regulatory role in the enzyme activity

Abstract: The γ-subunit of cyanobacterial and chloroplast ATP synthase, the rotary shaft of F1-ATPase, equips a specific insertion region that is only observed in photosynthetic organisms. This region plays a physiologically pivotal role in enzyme regulation, such as in ADP inhibition and redox response. Recently solved crystal structures of the γ-subunit of F1-ATPase from photosynthetic organisms revealed that the insertion region forms a β-hairpin structure, which is positioned along the central stalk. The structure–f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The β-hairpin domain is positioned along the central stalk of the F 1 part, and the top of this domain appears to interact with the “DELSEED” region of the catalytic subunit F 1 -β. The DELSEED region plays a central role in torque transmission ( 28 30 ), and its interaction with the β-hairpin domain results in the suppression of ATP hydrolysis activity in cyanobacterial F 1 -ATPase ( 31 , 32 ). It also enables efficient ATP synthesis by cyanobacterial F 0 F 1 ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…The β-hairpin domain is positioned along the central stalk of the F 1 part, and the top of this domain appears to interact with the “DELSEED” region of the catalytic subunit F 1 -β. The DELSEED region plays a central role in torque transmission ( 28 30 ), and its interaction with the β-hairpin domain results in the suppression of ATP hydrolysis activity in cyanobacterial F 1 -ATPase ( 31 , 32 ). It also enables efficient ATP synthesis by cyanobacterial F 0 F 1 ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results strongly suggested that the interaction between the DELSEED loop of the β subunit and the two amino acids located at the turn of the β-hairpin structure is sufficient to induce MgADP inhibition upon ATP hydrolysis. This model was supported by our studies using recombinant α 3 β 3 γ derived from T. elongatus with nick insertion into the proximal region of the β-hairpin structure (between V 222 and T 223 ) and cross-linking experiments using disulfide bond formation between the central stalk and the β-hairpin structure within the γ subunit ( 31 , 32 ).…”
mentioning
confidence: 60%
“…This was possibly explained by the interaction between the DELSEED region of the β subunit and a part of the γ subunit, although structural studies are necessary to prove this hypothesis. It was recently reported that the ε subunit of cyanobacterial F o F 1 has a different inhibitory mechanism compared with other organisms ( 41 ) and that the binding of the ε subunit caused a relative conformational change in the γ subunit ( 32 ). Consequently, the β-hairpin structure of the S. 6803 γ subunit, assisted by the ε subunit, might confer stiffness to the γ subunit and facilitate torque transmission during ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rotor ε -subunit that is attached to the γ -subunit and the c -ring ( Figure 1A /B) is observed in a retracted conformation that is not consistent with the ε -inhibition seen elsewhere in non-photosynthetic bacteria [ 29 , 67 , 71 - 73 ], where regulation involves the C-terminal part of the ε -subunit to reversibly interact with β -DELSEED in a so-called up-state (inhibited) or down-state (active) conformation [ 67 , 73 , 74 ]. In cyanobacteria though, the ε -subunit may be responsible for inducing the required conformational change in the γ -subunit to inhibit rotation in the ATP hydrolysis direction [ 72 , 75 ]. Structural studies of the cyanobacterial ATP synthase will help to identify which regulatory mechanisms play the most significant roles in cyanobacteria.…”
Section: Regulation Of Atp Synthases In Photosynthetic Organismsmentioning
confidence: 99%